Anti-inflammatory activity of ginger tablet Zingiber officinale Roscoe (Zingiberaceae) - Go, Ron Gilbert; Pineda, Allan Francis (2005)
The rhizomes of Zingiber officinale, which were obtained from Nueva Viscaya and available in all public market in Metro Manila, were used for this study. The alcohol-soluble constituents were extracted using the cold ethanol extraction method. Compatibility testing with different tablet ingredients was performed for one month and stability was evaluated using organoleptic observation. Afterwards, chemical stability with different excipients was determined by TLC analysis and the extracts were formed into tablets using the wet granulation method. The rhizome extract of Zingiber officinale was then investigated for anti-inflammatory and analgesic properties in Swiss albino mice. The extract produced significant (P<0.05) inhibition of the egg white--induced right hand paw inflammation in mice. The results show that rhizome extract of Zingiber officinale possesses anti-inflammatory properties. The dried extract was compatible with the formulation materials lactose, starch, and magnesium stearate. The tablets produced were dark brown in color and still has the characteristic aromatic, pungent odor of the rhizome extract.
Thesis (B.S. Industrial Pharmacy)--University of the Philippines Manila, 2005
Keywords: Ginger; Zingiberaceae